Allelopathic Influence of Sorghum Aqueous Extracts and Sorghum Powder on Germination Indices and Seedling Vigor of Hybrid Corn and Jungle Rice - YAR,S. (2020)
ABSTRACT: Allelopathy has become a paramount tool for controlling weeds in crop plants without deteriorating the environment. Allelopathic effects of sorghum aqueous extracts and sorghum powder on a single cross maize (Zea mays L.) hybrid “HC-8080” and a summer weed, jungle rice (Echinochloa colona L.) were assessed in the research laboratory of Agronomy, Faculty of Agriculture, Gomal University, Dera Ismail Khan, KPK, Pakistan. The treatments included: T1: control (untreated check), T2: sorghum aqueous extract at a rate of 5 mL kg-1 soil, T3: sorghum aqueous extract at a rate of 10 mL kg-1 soil, T4: sorghum aqueous extract at a rate of 15 mL kg-1 soil, T5: sorghum powder at a rate of 5 g kg-1 soil, T6: sorghum powder at a rate of 10 g kg-1 soil and T7: sorghum powder at a rate of 15 g kg-1 soil. The results unveiled that sorghum aqueous extract at a rate of 15 mL kg-1 soil was the most deleterious treatment which reduced the germination percentage (GP) in maize and E. colona by 23.57% and 47.03%, germination index (GI) by 22.30% and 42.14%, root length by 32.25% and 62.54% and shoot length by 23.22% and 62.76%, respectively over control. Similarly, 15 g kg-1 soil sorghum powder reduced the same parameters respectively by 18.85% and 41.09%, 15% and 33.53%, 9.3% and 54.69% and 15.88% and 45.34% in maize and E. colona, respectively and stood better than other powder treatments. Therefore it is concluded that sorghum extracts and powder can both be used to control weeds efficiently but their deleterious effect on the corresponding crop should also be an important consideration.